Validity of Umbilical Artery Doppler Ultrasound in Diagnosis of Intrauterine Growth Restricted Fetuses. - Birgis Fatima , Shazia Yusuf , Raja Amjad Mahmood (Journal of Rawalpindi Medical College, 2015)
Background: To determine the validity of the umbilical artery doppler ultrasound in the diagnosis of intrauterine growth restricted fetuses between 24 – 36 weeks using fetal birth weight as gold standard. Methods: In this cross sectional study a total of 108 pregnant women with growth restricted fetuses were studied. Doppler sonological assessment was done on abnormal umbilical artery waveform like decreased diastolic flow, absent and reversed diastolic flow, peak systolic / diastolic ratio> 3, pulsatility index > 0.98, resistive index >0.64. The results of umbilical artery Doppler ultrasound were compared with perinatal birth weight (gold standard). 2X2 table was used to find out true positive,true negative, false positive and false negative .Sensitivty, specificity,positive predictive value, negative predictive value and accuracy were determined to validate the results. Results: The age range of patients was from 18 years to 40 years(27.7 years ± 3.9 SD). Majority (53.7%) were true positives, 26.9% were true negatives, 10.1% were false positives and 9.3% were false negatives . Umbilical artery Doppler ultrasound had sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of 85.3%, 72.5%, 84.1%, 74.4% and 80.1% respectively. Doppler waveform (Absent or reversed) sensitivity ( 85.3%), specificity (72.5%),positive predictive value (84.1%),negative predictive value ( 74.4%) and over all accuracy (80.1%) validate the study results Conclusion: Umbilical artery Doppler ultrasound is an effective tool in early detection of IUGR fetuses.